Irish blood. [Series 1] [videorecording (DVD)] - Krizanc, John, 1956-; Ray, Christina (Acorn, 2025)
"After receiving a mysterious package from her estranged father, L.A. divorce lawyer Fiona Fox travels to Ireland to uncover the truth behind his disappearance. But as she pieces together the mystery behind his past, she finds herself entangled in a family history she never knew, filled with secrets, deception, and danger."--